SALES INFORMATION SYSTEM FOR BAKMI KHEK RESTAURANT USING SYSTEM DEVELOPMENT LIFE CYCLE METHODOLOGY - Syerlina Fadila Dirman; Helen Syerah; Hadi Supratikta (PT. Jurnal Center Indonesia Publisher, 2024)
Sales Information System (SIP) is an integral part of business operations in the food and beverage industry. This research aims to develop a SIP specifically for Bakmi Khek Restaurant. The System Development Life Cycle (SDLC) methodology was chosen as the framework for the development of this system. This approach allows for structured stages, from planning to maintenance, that are in line with business needs. The research started with the planning stage which involved analyzing user requirements and formulating system objectives. Next, a system analysis stage was conducted to understand the business processes, information flow, and functional requirements of the system. The next system design stage establishes the architecture and technical specifications of the system. System implementation is done after the design is complete, followed by a testing phase to ensure system functionality and reliability. The result of this research is an SIP that is integrated with the sales activities of Bakmi Khek Restaurant. The system includes features such as inventory management, order recording, and sales tracking. Through the application of SDLC, the development of this system can be done in a structured and efficient manner, ensuring business needs are met optimally.